Metabolites in animal feed. - Foo, Hooi Ling; Loh, Teck Chwen; Karunakaramoorthy, Anuradha; Shamsudin, Mariana Nor; Abdul Rahim, Raha (2009)

(untitled)
The present invention relates to an aquatic animal feed product comprising metabolite derived from probiotic LAB. Hence, such a feed product is highly suitable for use a feed product for an aquatic animal.